Remote Sensing Analysis of Recent Carbonate Platforms, East of Sabah: Potential Analogues for Miocene Carbonate Platforms of the South China Sea - Aicha Chalabi; B. Pierson; Jasmi Ab Talib (Geological Agency, 2012)
DOI: 10.17014/ijog.v7i3.141Recent carbonate platforms may provide useful analogues for fossil platforms and reefs, and could allow the generation of quantitative tools for the prediction of facies distribution, reservoir volumes, and reservoir quality. Data from these modern analogues would greatly enhance our ability to construct more reliable and calibrated reservoir models for carbonate fossil fields, such as the Miocene carbonate platforms of Central Luconia Province, Sarawak. In this study, carbonate facies maps and quantitative reservoir data will be generated by using remote sensing techniques. Satellite imageries over the carbonate platforms east of Sabah have been acquired and processed for generating facies maps. In order to produce a reliable facies map, the composition and grain size distribution of the sediments that make up individual facies must be known in order to determine the classes that have been identified on the initial facies maps. Samples collected from the Gaya and Selekan platforms were analyzed and the results of grain size analysis are illustrated.